Synthesis and Characterization of Metal Sulfides Nanoparticles/Poly(methyl methacrylate) Nanocomposites - Peter A. Ajibade; Johannes Z. Mbese (International Journal of Polymer Science)
Metal sulfides nanoparticles in poly(methyl methacrylate) matrices were prepared and characterized by infrared spectroscopy, thermogravimetric analysis, powder X-ray diffraction, scanning electron microscope (SEM), and transmission electron microscope (TEM). The FTIR confirms the dispersion of the nanoparticles in PMMA matrices with the C=O and C–O–C bonds of the PMMA shifting slightly which may be attributed to the interactions between the nanoparticles and PMMA. The ZnS nanoparticles in PMMA have average crystallite sizes of 4–7 nm while the CdS has particle size of 10 nm and HgS has crystallite sizes of 8–20 nm. The increasing order of particle sizes as calculated from the XRD is ZnS/PMMA<HgS/PMMA<CdS/PMMA and ranges from 1.02 to 1.35 nm. These calculated particle sizes are smaller than the values obtained from TEM.